Pirfenidone as a potential antifibrotic injectable for Dupuytren's disease. (7th February 2022) - Panigrahi, Suchitra; Barry, Amanda; Multner, Scott; Kasting, Gerald B.; Figueroa, Julio A. Landero; Satish, Latha; Kumari, Harshita
Abstract: Dupuytren's disease is a progressive fibrotic condition of the hand that causes contracture of fingers in later stages. Our previous in vitro studies suggest that the transformation of fibroblasts to myofibroblasts induced by transforming growth factor-beta can be inhibited by the addition of the antifibrotic drug, pirfenidone (PFD). We hypothesize that the local delivery of PFD directly to nodules can potentially prevent the progression to cords and, furthermore, that injection of PFD after the resection of cords can limit the recurrence of the disease. The purpose of this research was to develop a PFD injectable solution and to assess its safety in mice. Based on preformulation observations, a sterile solution containing up to 8 mg/0.4 mL of PFD was prepared in a phosphate buffer with and without 15%v/v N-methyl-2-pyrrolidone. Accelerated stability studies suggested that the product should be kept at refrigerated temperature (2–8 °C) for long-term storage. Safety studies involving subcutaneous administration to mice showed that 2–4 mg of PFD in 0.4 mL aqueous buffer did not elicit a significant inflammatory reaction. However, 4 mg PFD in 0.4 mL (FB ) of buffer: NMP cosolvent system led to a significant increase in the influx of inflammatory cells and 8 mg PFD (FA ) in the cosolvent system was lethal to the animals.